Modeling Banias Refinery Treatment Plant using the GPS-X (Latakia University Journal -Engineering Sciences Series, 2019)
Banias Refinery is one of the two oil refineries in Syria, which has been effectively depended on through the Syrian crisis. Since the wastewater generated by Banias refinery is complex in terms of its contents, it has different types of treatment such as physical, chemical and biological treatment. Hence, our role in conducting a study to evaluate the performance of the wastewater treatment plant to make sure that it operates adequately. Because of the importance of  the modeling processes, we studied the biological treatment plant and identified the components of wastewater by taking different samples and using the respiratory techniques in the wastewater laboratory of the Higher Institute of Applied Sciences and Technology, Damascus. Depending on GPS-X modeling and simulation software, the application of ASM3 model has achieved good results by representing the performance of the plant and its simulation, the output simulation values ​​were agreed with the measured data in terms of TSS, VSS and COD. Results indicated the death of bacteria and presence of high inert organic matter in the plant wastewater. مصفاة بانياس هي إحدى مصفاتي النفط الوحيدتين في سوريا، والتي اعتمد عليها كثيرا خلال الأزمة السورية، ونظرا لكون مياه الصرف الناتجة عن مصفاة بانياس هي مياه صرف صناعية معقدة من حيث محتوياتها، فهي تخضع للمعالجة الفيزيائية والكيمائية والبيولوجية. تم اجراء دراسة لتقييم أداء محطة المعالجة البيولوجية للتأكد من سيرورة عملها بشكل جيد، وذلك بالاعتماد على نماذج الحمأة النشطةASM  التي تساعد في عملية التقييم بشكل فعال ، ونظرا لأهمية النمذجة درسنا واقع محطة المعالجة البيولوجية لمصفاة بانياس، وقمنا بتحديد مكونات مياه الصرف فيها من خلال أخذ عينات متعددة واستخدام تقنيات النشاط التنفسي في تجزئه مياه الصرف الصحي في مخابر المعهد العالي للعلوم التطبيقية والتكنولوجيا بدمشق، ومن ثم تم بناء نموذج محطة المعالجة المقترح باستخدام برنامج النمذجة والمحاكاة GPS-X ، فقد حقق تطبيق النموذج ASM3 نتائج جيدة من خلال تجسيد عمل المحطة ومحاكاة واقعها، حيث اتفقت قيم محاكاة النموذج مع البيانات المقاسة في وقت أخذ العينات  من حيث الـ TSS ، VSS ، COD  وأظهرت النتائج موت بكتيريا الهيتروفاز و تواجد المواد العضوية الخاملة بنسبة عالية في مياه صرف المحطة.